The development of reindeer husbandry in Canada - Treude, Erhard (Polar Record, 1968)
The first reindeer were introduced into Canada for humanitarian rather than commercial reasons. Encouraged by the success achieved in Alaska, where 1280 reindeer imported by Dr Sheldon Jackson from Siberia between 1892 and 1902 had increased in a few years to several times that number, the missionary physician of Labrador, Wilfred Grenfell, hoped to develop a reindeer meat-and-dairy industry in his region, where tuberculosis was common and infant mortality high. In 1908, with financial support from the Boston Transcript and the Canadian Department of Agriculture, he bought 300 reindeer in Norway and brought them to St Anthony, Newfoundland. Under the supervision of four Lapp herders, the animals quickly adjusted to their new environment